The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0082580
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Contribute to Heterogeneity of IL-17 Producing Cells in Rheumatoid Arthritis and Healthy Controls

Abstract: Secretion of the proinflammatory cytokine Interleukin-17A (IL-17A) is the hallmark of a unique lineage of CD4 T cells designated Th17 cells, which may play a crucial role in the pathogenesis of rheumatoid arthritis (RA) and many autoimmune diseases. Recently, IL-17-producing cells other than T cells have been described, including diverse innate immune cells. Here, we show that the cellular sources of IL-17A in RA include a significant number of non-T cells. Multicolour fluorescence analysis of IL-17-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…76 Evidence suggests that B cells contribute to RA pathology by producing autoantibodies that initiate the complement cascade and promote selective antigen uptake. 77 In addition, B cells also present antigen to T cells, provide co-stimulation, release inflammatory cytokines 78,79 and contribute to RA-associated osteoclast activation and bone destruction through expression of RANKL. 80,81 Lack of IL-10 + regulatory B (B REG ) cell activity, through low frequencies or defective function, has also been suggested to contribute to RA.…”
Section: B Cellsmentioning
confidence: 99%
“…76 Evidence suggests that B cells contribute to RA pathology by producing autoantibodies that initiate the complement cascade and promote selective antigen uptake. 77 In addition, B cells also present antigen to T cells, provide co-stimulation, release inflammatory cytokines 78,79 and contribute to RA-associated osteoclast activation and bone destruction through expression of RANKL. 80,81 Lack of IL-10 + regulatory B (B REG ) cell activity, through low frequencies or defective function, has also been suggested to contribute to RA.…”
Section: B Cellsmentioning
confidence: 99%
“…Thus our data of increased IL-17 production by NK cells of ERA patients may support this hypothesis since most of our patients were HLA B27 positive and had high KIR3DL1/2 expression. A study in RA has reported a large fraction of IL-17 producing non T cells as compared to controls, among these cells NK cells also formed a small proportion [28]. No data however is available on spondyloarthropathies.…”
Section: Discussionmentioning
confidence: 99%
“…1 This pro-inflammatory marker has been associated with the pathogenesis of several autoimmune diseases and human inflammatory conditions. 1 The current evidence suggests that IL-17A is involved in psoriasis, 7 rheumatoid arthritis, 8 multiple sclerosis, 9 inflammatory bowel diseases 10 and asthma. 11 Several studies have demonstrated the association between dietary factors and inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%